PspG, a New Member of the Yersinia enterocolitica Phage Shock Protein Regulon - Green, Rebecca C. (American Society for Microbiology, 2004)
The Yersinia enterocolitica phage shock protein (Psp) system is induced when the Ysc type III secretion system is produced or when only the YscC secretin component is synthesized. Some psp null mutants have a growth defect when YscC is produced and a severe virulence defect in animals. The Y. enterocolitica psp locus is made up of two divergently transcribed cistrons, pspF and pspABCDycjXF. pspA operon expression is dependent on RpoN (σ(54)) and the enhancer-binding protein PspF. Previous data indicated that PspF also controls at least one gene that is not part of the psp locus. In this study we describe the identification of pspG, a new member of the PspF regulon. Predicted RpoN-binding sites upstream of the pspA genes from different bacteria have a common divergence from the consensus sequence, which may be a signature of PspF-dependent promoters. The Y. enterocolitica pspG gene was identified because its promoter also has this signature. Like the pspA operon, pspG is positively regulated by PspF, negatively regulated by PspA, and induced in response to the production of secretins. Purified His(6)-PspF protein specifically interacts with the pspA and pspG control regions. A pspA operon deletion mutant has a growth defect when the YscC secretin is produced and a virulence defect in a mouse model of infection. These phenotypes were exacerbated by a pspG null mutation. Therefore, PspG is the missing component of the Y. enterocolitica Psp regulon that was previously predicted to exist.